Making Worlds, Worlding Metaverses A Comparative Study of Metaverse Developers and Users in Italy - Iapaolo, Fabio; Pingitore, Marcus (Funes. Journal of narratives and social sciences, 2026)
This article examines how the metaverse is locally enacted and imagined in Italy, offering a situated perspective that moves beyond dominant corporate framings. While existing research has documented how platform power around the metaverse is consolidated by firms such as Meta, Apple, and Nvidia, far less attention has been paid to actors, practices, and contexts that remain largely off the map of both global metaverse narratives and the critiques directed at them. Drawing on ethnographic fieldwork that combines in-person and in-metaverse research with Italian developers and user communities, the study explores how the metaverse is defined, practised, and made meaningful within Italy’s mid-level innovation economy. Through the notion of worlding, we trace how global metaverse narratives are appropriated, modified, or unevenly engaged with in practice, giving rise to a plurality of actually existing metaverses shaped by divergent temporalities, value regimes, and infrastructural dependencies. In doing so, the article contributes to decentring dominant imaginaries of digital futures by showing how the metaverse takes form through situated negotiations within – rather than outside of – global platform power.